2023
DOI: 10.1007/s00330-023-10403-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of contrast medium for transcatheter aortic valve replacement planning using a spectral detector CT: a prospective clinical trial

Isabel L. Langenbach,
Marcel C. Langenbach,
Thomas Mayrhofer
et al.

Abstract: Introduction This study investigated the use of dual-energy spectral detector computed tomography (CT) and virtual monoenergetic imaging (VMI) reconstructions in pre-interventional transcatheter aortic valve replacement (TAVR) planning. We aimed to determine the minimum required contrast medium (CM) amount to maintain diagnostic CT imaging quality for TAVR planning. Methods In this prospective clinical trial, TAVR candidates received a standardized dual-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They found high objective image quality and a significant reduction in radiation dose with DECT. Finally, Langenbah et al [29] studied four patient groups using four different contrast medium doses (60, 50, 40, and 30 mL) and conducted both subjective and objective image evaluations. They determined that 40 keV was the energy level with better results, allowing for a reduction in contrast medium down to 40 mL without compromising diagnostic image quality.…”
Section: Discussionmentioning
confidence: 99%
“…They found high objective image quality and a significant reduction in radiation dose with DECT. Finally, Langenbah et al [29] studied four patient groups using four different contrast medium doses (60, 50, 40, and 30 mL) and conducted both subjective and objective image evaluations. They determined that 40 keV was the energy level with better results, allowing for a reduction in contrast medium down to 40 mL without compromising diagnostic image quality.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in contrast volume is a significant advantage in clinical practice, particularly for patients with renal dysfunction and other comorbidities. Langenbach et al [34] conducted a study utilizing a dual-energy spectral detector and virtual monoenergetic imaging reconstruction in 60 patients undergoing pre-interventional transcatheter aortic valve planning. The results revealed that reducing the contrast volume to 40 mL did not degrade image quality.…”
Section: Is Pcd-ct Capable Of Decreasing the Amount Of Contrast Agent...mentioning
confidence: 99%